ESTUDO COMPARATIVO DA ENERGIA GERADA POR PLACAS FOTOVOLTAICAS COM RELAÇÃO À TEMPERATURA, UTILIZANDO SISTEMAS DE RESFRAMENTO - Gabriel Ozorio Linhares de Mello (2021)
The world energy matrix is composed of several primary sources, among which the fossil fuels, such as oil, prevail over the others. However, due to population growth, humanitarian crises, and industrial and technological development, there will be increasing demands for renewable energy. Among these, the photovoltaic (PV) solar energy stands out, as it enables generation in a clean and decentralized manner. Brazil has the advantage of being located in an intertropical zone that registers high levels of solar radiation throughout the year, unlike other countries where this technology is more consolidated. Likewise, studies on the conversion of solar energy into electrical energy have shown that there are factors that reduce the energy production of the PV board, including temperature. Thus, in order to contribute to the improvement of photovoltaic modules, a comparative study was carried out in this work to analyze the output power performance of a photovoltaic system being cooled by external devices. In the experiment, two 51 watt polycrystalline silicon panels were installed, independent of each other; being a control board and a test board. The control module is the reference module, subject to ambient temperature and without any refrigeration system. In the tested module, three different cooling devices were installed separately. Initially, these modules were compared for the same working conditions and verified that they present energy production within the values established by the manufacturer, ensuring that the comparative studies in the field are reliable. To remove the heat, the devices used were: a fan, sometimes acting on the surface and sometimes on the back of the plate; a Peltier thermoelectric module on the back of the board; and pumping water on the module surface. The results show that the energy output of the modules with ventilation, Peltier, and surface water were 2.11%, 2.24%, and 3.92% higher than the control board, respectively. Therefore, it is possible to identify that there are possibilities to maximize the efficiency of the board by installing devices that can cool the board without damaging the power generation.